Реологические особенности при подаче пены пеногенерирующими системами со сжатым воздухом - Karpenchuk, Игорь; Grachulin, Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
The work describes the mathematical model of movement of gas-water mix at one-dimensional movement. The equations of movement of gas-water mix are integrated with rheological features of solutions of foam concentrate. The engineering design procedure of losses of pressure is described at foam supplying in Compressed Air Foam Systems.